IMPLIKASI PERKAWINAN USIA DINI DI BANJAR AUMAN BUKIT MUNDUK TIYING DESA PELAGA KECAMATAN PETANG KABUPATEN BADUNG - Astrini, Ni Made Yogi; Sumantra, I Nengah; Diana Putra, I Gede Dedy (UPADHYAYA: JURNAL PENELITIAN PENDIDIKAN, 2023)
Early marriage is a physical and spiritual relationship between men and women in the household at a young age.  Early marriage that occurred at Auman Bukit Munduk Tiying Banjar is an event that is contrary to religious teachings and law No. 16 article 7 of 2019. Based on this background, the formulation of the problem in this study is: 1. What are the factors-factors that cause early marriage at Auman Bukit Munduk Tiying hamlet, Pelaga Village, Petang District, Badung Regency, 2. What are the implications of implementing early marriage at Auman Bukit Munduk Tiying hamlet, Pelaga Village, Petang District, Badung Regency, 3  How are the efforts of the village government or community in anticipating early marriage at the Auman Bukit Munduk Tiying hamlet, Pelaga Village, Petang District, Badung Regency.  The research method used is qualitative research with a phenomenological approach.  The theoretical basis is the theory of social change, the theory of behavior change (behavioristic), and the theory of symbolic interactionism.  The informant determination technique is purposive.  Data collection techniques are interviews, literature, observation, and documentation.  The results of this study found that 1) the occurrence of early marriage in hamlet Auman Bukit Munduk Tiying was a result of internal and external factors, 2) the implications of early marriage that occurred were implications for education, psychology, reproductive health, religious, moral, social,  and law 3) the efforts of the village government or the community in anticipating early marriage are by providing outreach to the community regarding the implications of early marriage, the role of parents in protecting and reminding their children and reminding them of the laws and regulations that have been made by the government.  Keywords: Implications, Early Marriage